Exome sequencing links CEP120 mutation to maternally derived aneuploid conception risk. Issue 9 (9th August 2020) - Tyc, Katarzyna M; El Yakoubi, Warif; Bag, Aishee; Landis, Jessica; Zhan, Yiping; Treff, Nathan R; Scott, Richard T; Tao, Xin; Schindler, Karen; Xing, Jinchuan
Abstract: STUDY QUESTION: What are the genetic factors that increase the risk of aneuploid egg production? SUMMARY ANSWER: A non-synonymous variant rs2303720 within centrosomal protein 120 ( CEP120 ) disrupts female meiosis in vitro in mouse. WHAT IS KNOWN ALREADY: The production of aneuploid eggs, with an advanced maternal age as an established contributing factor, is the major cause of IVF failure, early miscarriage and developmental anomalies. The identity of maternal genetic variants contributing to egg aneuploidy irrespective of age is missing. STUDY DESIGN, SIZE, DURATION: Patients undergoing fertility treatment (n = 166) were deidentified and selected for whole-exome sequencing. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients self-identified their ethnic groups and their ages ranged from 22 to 49 years old. The study was performed using genomes from White, non-Hispanic patients divided into controls (97) and cases (69) according to the number of aneuploid blastocysts derived during each IVF procedure. Following a gene prioritization strategy, a mouse oocyte system was used to validate the functional significance of the discovered associated genetic variants. MAIN RESULTS AND THE ROLE OF CHANCE: Patients producing a high proportion of aneuploid blastocysts (considered aneuploid if they missed any of the 40 chromatids or had extra copies) were found to carry a higher mutational burden in genes functioning in cytoskeleton and microtubule pathways. Validation of the functional significance of a non-synonymous variant rs2303720 within Cep120 on mouse oocyte meiotic maturation revealed that ectopic expression of CEP120:p.Arg947His caused decreased spindle microtubule nucleation efficiency and increased incidence of aneuploidy. LIMITATIONS, REASONS FOR CAUTION: Functional validation was performed using the mouse oocyte system. Because spindle building pathways differ between mouse and human oocytes, the defects we observed upon ectopic expression of the Cep120 variant may alter mouse oocyte meiosis differently than human oocyte meiosis. Further studies using knock-in 'humanized' mouse models and in human oocytes will be needed to translate our findings to human system. Possible functional differences of the variant between ethnic groups also need to be investigated. WIDER IMPLICATIONS OF THE FINDINGS: Variants in centrosomal genes appear to be important contributors to the risk of maternal aneuploidy. Functional validation of these variants will eventually allow prescreening to select patients that have better chances to benefit from preimplantation genetic testing. STUDY FUNDING/COMPETING INTEREST(S): This study was funded through R01-HD091331 to K.S. and J.X. and EMD Serono Grant for Fertility Innovation to N.R.T. N.R.T. is a shareholder and an employee of Genomic Prediction. TRIAL REGISTRATION NUMBER: N/A.